Tripartite evolutionary game analysis and simulation research on zero-carbon production supervision of marine ranching against a carbon-neutral background - Liang, Jinshui; Zhang, Maomao; Yin, Zengqiang; Niu, Keru; Li, Yuan; Zhi, Kaiting; Huang, Shengnan; Yang, Jun; Xu, Min (Frontiers in Ecology and Evolution, 2023)
Theoretically and practically, studying the zero-carbon production supervision of marine ranching is crucial to the attainment of my country's fishery carbon peak and carbon neutral goals. This study introduces a third-party detection agency to construct a tripartite evolutionary game model based on the possibility of problems such as a lack of government supervision and imperfect detection mechanisms, through an analysis of the evolution stability and evolution path of each participant's strategy choice, the mechanism of each element's influence on the tripartite strategy choice is revealed, as well as the evolution law of the tripartite game. The results indicate that: ① The change in strategic choice of each participant is significantly influenced by the change in strategic choice of the other participants, and the comprehensive consideration of the maximization of the comprehensive value of each participant is conducive to the development of all three parties. ② Government efforts to increase low-carbon subsidies and penalties will aid in promoting the normative behavior of zero-carbon production by marine ranching businesses and the rejection of rent-seeking by third parties. ③The accountability of higher-level governments for the dereliction of duty of regulatory agencies is particularly important to enhance the robustness of zero-carbon production of marine ranching enterprises.Last but not least, a Matlab-based numerical simulation analysis of the evolutionary stability equilibrium of the model was conducted, and based on the carbon balance of marine ranching enterprises, countermeasures and recommendations were made to the government to improve the zero-carbon production supervision mechanism of marine ranching. In order to provide reference for the development of the marine ranching industry and promote the realization of zero emissions in the production activities of the marine ranching industry.